MODERN METHODS OF TREATMENT OF CHRONIC RENAL FAILURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Chronic renal failure (CKD) is a progressive condition characterized by a prolonged decline in kidney function and requiring constant medical monitoring. Modern treatments for CKD include drug therapy, dialysis, and kidney transplantation. This article discusses current approaches to the treatment of CKD, based on the analysis of data from scientific sources, such as Google Scholar, Scopus and other peer-reviewed databases. The main methods of therapy, their effectiveness and the results of clinical trials are described. It has been revealed that an integrated approach to treatment, including new medications, improved dialysis methods and modern transplantation technologies, can significantly improve the quality of life of patients and slow down the progression of the disease. The work highlights the importance of continuous monitoring and individualization of treatment to achieve the best outcomes.